Inner ear lesion and the differential roles of hypoxia and hypercarbia in triggering active movements: Potential implication for the Sudden Infant Death Syndrome. (19th November 2016) - Ramirez, Sanja; Allen, Travis; Villagracia, Lindsay; Chae, Yooree; Ramirez, Jan M.; Rubens, Daniel D.
Highlights: Infants that succumb to SIDS have been described with inner ear dysfunction at birth and on autopsy. Hypoxia is the trigger for the movement response while carbon dioxide suppresses it. Carbon dioxide does not trigger active movements under natural sleep conditions. A degree of intact inner ear function is necessary for instigating an active movement response. Abstract: Infants that succumb to Sudden Infant Death Syndrome (SIDS) have been identified with inner ear dysfunction (IED) at birth and on autopsy. We previously investigated whether IED could play a mechanistic role in SIDS. We discovered that animals with IED displayed significant suppression of movement arousal to a hypoxic–hypercarbic gas mixture under light anesthesia. In the current study we investigated the role of each gas in triggering movements and the response to hypercarbia during natural sleep without anesthesia. Seventeen-day-old CD-1 mice received intra-tympanic gentamicin (IT-Gent) injections to precipitate IED. The movement response to hypercarbia, hypoxia and hypoxia-hypercarbia was compared to controls under light anesthesia. Hypercarbia did not stimulate vigorous movements in any animals under either sleep condition. Hypoxia triggered vigorous movements in controls ( p  < 0.05) and a decreased response in IT-Gent animals under light anesthesia. This contrasted with combined hypoxia-hypercarbia, in which IT-Gent animals displaced significantly suppressed movements compared to controls ( p  < 0.05). Our findings portray that a degree of intact inner ear function is necessary for instigating the movement response. Additionally, hypoxia is the trigger for the movement response while carbon dioxide (CO2 ) suppresses it. The finding that carbon dioxide did not stimulate movement during natural sleep is an important finding. This contrasts with other studies that have identified hypercarbia as an arousal stimulus with EEG. Further studies are warranted to evaluate the precise role of the inner ear in the movement response and potential association with SIDS. The early detection of IED in SIDS predisposed cases could be invaluable.